Reconstructing Islam: Muslim Education and Literature in Ming-Qing China (American Journal of Islam and Society, 2006)
During the sixteenth century when Islam was already established in China, Chinese Muslims began to critically examine their understanding of Islamic knowledge and how to transmit it to future generations. Traditional tutelage based on purely Arabic and Persian sources generally evaded a Muslim population that, for the most part, could no longer read the available rare Islamic texts. The subsequent reconstruction of Islamic knowledge and education emphasized the intersections between the Chinese and the Muslim communities’ cultural and religious heritages. The new specialized educational system, “scripture hall education” (jingtang jiaoyu), utilized Chinese as the language of instruction and incorporated aspects of traditional Chinese literati education in collaboration with newly retrieved Islamic sources from the Muslim heartland. The ensuing standardization and organization of curriculum and pedagogical techniques enabled peripatetic students to replicate this system throughout China. It also allowed the religious community’s leaders to direct the discourse concerning Islam and disseminate a specific interpretation of religious knowledge. This is most clearly displayed through the Han Kitab, the canonized corpus of Chinese Islamic texts written, approximately, during 1600-1750. This literature articulated Islamic principles through the lexicon of literary Chinese and replicated the ideology highlighted by the educational network. This paper analyzes why Islamic knowledge was lost and traces how the new educational system transformed the indigenous Islamic discourse, articulated through the Han Kitab literature, to reflect a distinctive Chinese Muslim interpretation of the faith.